Prognostic impact of primary versus secondary resistance to sorafenib in patients with HCC - Jin Lei; Hongyuan Dai; Ya Zhang; Guangling Ou; Zhi Peng Liang; Yinying Lu; Haiyang Li (Therapeutic Advances in Medical Oncology)
Background: Sorafenib is a first-line treatment option for patients with hepatocellular carcinoma (HCC). However, the impact of sorafenib resistance type on patient survival prediction and choice of second-line treatment regimen is unknown. Objectives: This study aims to explore the factors predicting resistance in patients with HCC receiving sorafenib, the impact of resistance on survival, and the optimal second-line treatment regimen. Design: This was a retrospective cohort study. Methods: We recruited all patients with advanced HCC who received first-line sorafenib from January 2019 to January 2023 in two medical centers in China. They were divided into primary and secondary resistance groups according to tumor progression within 3 months. Resistance was the primary outcome of this study. The secondary outcomes were progression-free survival (PFS) and overall survival (OS). Results: A total of 424 patients met the inclusion criteria, including 165 patients (38.9%) in the primary group and 259 patients (61.1%) in the secondary group. The independent risk factors for primary resistance were alpha-fetoprotein (AFP) > 400 ng/mL and alanine aminotransferase (ALT) > 40 U/L. Patients in the primary group had significantly shorter median OS than those in the secondary group (9.0 months vs 23.0 months, p  < 0.001). Compared with tyrosine kinase inhibitor (TKI) monotherapy, the use of TKI plus PD-1 inhibitor combination therapy as second-line treatment conferred a longer median PFS (6.0 vs 10.0 months, p  < 0.001) and OS (13.0 vs 22.0 months, p  < 0.001). Conclusion: Sorafenib has a high incidence of primary resistance and short survival in patients who develop primary resistance. AFP and ALT are influential factors in primary resistance, and it is valuable to use these two metrics to guide the use of sorafenib. As second-line therapy, a TKI plus PD-1 inhibitor regimen should be preferentially recommended.